059 Teratoma with glycine, NMDA & VGKC antibodies presenting with severe weakness, respiratory failure & corticospinal tract dysfunction. Issue 6 (24th May 2018) - Swayne, Andrew; O'Gorman, Cullen; Sheikh, Nabeel; Brown, Helen; Buck, Lyndall; Prain, Kerri; Gillis, David; Wong, Richard; Blum, Stefan
Abstract : Introduction: Glycine antibodies are associated with progressive encephalomyelitis with rigidity and myoclonus (PERM) but have been rarely reported to cause myasthenic-like symptoms. 1 We present a single patient seen at a tertiary neurology centre with fatigable muscle weakness and corticospinal tract dysfunction with positive glycine, VGKC and NMDA receptor antibodies, associated with an ovarian teratoma expressing neural tissue. Case: A 32 year old female presented with fatigable muscle weakness. Physical examination was atypical for a disease of the neuromuscular junction with features of exaggerated reflexes and clonus. The weakness progressed over 1–2 weeks leading to respiratory failure. Investigations including MRI brain, repetitive stimulation and acetylcholine-receptor antibody studies were all within the normal limits. Studies for neuronal antibodies against intracellular targets were negative. Further investigation revealed positive autoantibodies against Glycine receptor, NMDA (N-Methyl-d-aspartate) receptor and VGKC (voltage-gated potassium channel) with an underlying ovarian teratoma. Complete clinical resolution was achieved with teratoma resection and 2 g/kg course of intravenous immunoglobulin. Histopathological examination of the tumour revealed a mature cystic teratoma with dystrophic calcification. The teratoma included skin, adipose tissue, intestinal type mucosa, and neuroglial tissue in which nerve fibres and ganglion cells are present. A lymphoid infiltrate was concentrated in areas of neural tissue within the teratoma. Conclusion: Muscle weakness, corticospinal tract dysfunction and respiratory failure have previously been reported in the context of anti-glycine antibodies. This is the first case where anti-glycine, anti-NMDA and anti-VGKC antibodies have been found in the context of an ovarian teratoma. The autoimmune nature of this condition is emphasised by the lymphoid infiltrate around the neural tissue expressed within the teratoma. Reference: 1. Carvajal-Gonzalez A, Leite MI, Waters P, Woodhall M, Coutinho E, Balint B, … Vincent A. Glycine receptor antibodies in PERM and related syndromes: characteristics, clinical features and outcomes. Brain2014;137(Pt 8):2178–2192.